Keberadaan dan Karakteristik Endapan Drat Kuarsa Epitermal di Gunung Tukung, Kabupaten Pacitan, Jawa Timur: Implikasi pada Eksplorasi Emas di Pegunungan Selatan - , A. Idrus ([Yogyakarta] : Departemnts of Geological Engineering Faculty of E, 2009)
Mt. Tukung Area, situated in Pacitan District, East Java is one of several gold prospect areas in the Southern areas Mountain Range in Java, Indonesia. Two types of intrusive rocks identified in Mt. Tukung are andesite intrusive and dacite intrusive, exposed in a half-circular depression where volcanic breccia and tuff are widely distributed. The occurrences of quartz texture, alteration hydrothermal minerals, ore mineralization show low sulphidation type. This is also supported by microhermometric fluid inclusion data of quartz vein showing low salinity (between 0.3-2.2 wt.% NaCl eq) and temperature (Th) ranges of 195-277&deg